Saturday Morning, Voortrekker Road, Maitland - Vessié, Margaux (WritingThreeSixty, 2018)
These three portraits are the results of an excursion on Voortrekker Road with one of my classmates, Clotilde, who is also from France. I have to say that it took a certain amount of bravery for us to get there, two white female foreigners in this neighbourhood that was not ours. But this special Saturday morning was bright and sunny and people were enjoying the sun outside. We were just walking on the road, hiding our cameras in their big black bags. But once they were out, people came to us, asking to be photographed.